Exploring the use of and perceptions about honey as complementary and alternative medicine among the general public in the state of Selangor, Malaysia - Mohd Shahezwan Abd Wahab, Noordin Othman, Noor Hazwani Izzati Othman, Amirah Adhwani Jamari, Aida Azlina Ali (Journal of Applied Pharmaceutical Science, 2017)
Objective: Honey has been used as a biologically-based complementary and alternative medicine (CAM) since ancient times. The present study aimed to explore the use of and the perceptions about honey as a CAM among the general public in Selangor.Method: A cross-sectional study using a self-completed questionnaire was employed. Participants were recruited using convenience sampling method from three towns in the state of Selangor.Results: 56 % (168/300) of respondents used honey as CAM. Most users used honey as a dietary supplement for well-being (71.4 %, 120/168), or to treat coughs (57.1%, 96/168), and sore throats (53 %, 89/168). A small percentage of users (13.1 %, 22/168) used honey to treat asthma. The respondents generally showed favourable perceptions about honey as CAM as more than 60 % of them rated strongly agree and agree for each of the perception item in the survey. The users obtained their supply of honey from supermarkets (42.3%, 71/168), grocery stores (32.7 %, 55/168), and friends/family (31%, 52/168). In addition, most users sought information about honey from friends/family (63.1 %, 106/168), the Internet (60.7 %, 102/168) and advertisements (39.3 %, 66/168).Conclusion: The respondents generally had favourable perceptions about honey as CAM. Future work should aim to produce more scientific evidences of the benefits and safety of honey. The use of honey supplies from unreliable sources as CAM and unreliable sources of information as well as potential self-medication with honey for serious diseases should raise concerns.
Keywords: Complementary and alternative medicine, honey, Malaysia, perceptions, survey.